Prevalence of asymptomatic Plasmodium vivax infections in Pozo Colorado, northeastern Venezuela: a cross-sectional study - Albina Wide; Sergia Blondell; Jacinta Capaldo; Rosalba Pabón; Darío González; Oriana A. Regalado-Gutiérrez; Fhabián S. Carrión-Nessi; David A. Forero-Peña; Octavio Fernandes; Oscar Noya (Discover Public Health)
Abstract Background Plasmodium spp. infections that do not cause clinical manifestations of malaria serve as silent sources of infection that maintain transmission in endemic areas, negatively impacting efforts to control this parasitic disease. Despite the substantial increase in malaria cases in recent years, studies on the prevalence of asymptomatic infections in Venezuela remain limited. Methods A cross-sectional study was conducted in 2006 in Pozo Colorado, Sucre State, an area within the eastern malaria focus. Sociodemographic and epidemiological data were collected from asymptomatic individuals. Parasitological diagnostic tests included thick blood smear microscopy, blood smear extension, immunological rapid diagnostic tests (RDTs), and molecular biology using nested polymerase chain reaction (PCR). Results A total of 177 individuals were evaluated. Their median age was 22 (IQR 13–35) years, and 67.8% had lived in the area for over 10 years. Two-thirds (66.1%) reported a history of malaria, with a median of 2 (IQR 1–3) previous episodes caused by P. vivax. A total of 23 (13%, 95% CI = 8.7–18.5) individuals tested positive for P. vivax by PCR. Prevalence was higher among men over 18 years (14.6%, 95% CI = 8.3–23.5). No significant differences were observed between the sociodemographic characteristics or malaria history of PCR-positive and PCR-negative individuals. Conclusion The prevalence of asymptomatic P. vivax infections in Pozo Colorado, Sucre state, highlights the need for active case detection in other malarial foci. Using more sensitive diagnostic techniques as part of the national malaria control program would enable the provision of specific antimalarial treatments to interrupt disease transmission.